2022
DOI: 10.1111/acel.13680
|View full text |Cite
|
Sign up to set email alerts
|

Sirt1 overexpression improves senescence‐associated pulmonary fibrosis induced by vitamin D deficiency through downregulating IL‐11 transcription

Abstract: Determining the mechanism of senescence‐associated pulmonary fibrosis is crucial for designing more effective treatments for chronic lung diseases. This study aimed to determine the following: whether Sirt1 and serum vitamin D decreased with physiological aging, promoting senescence‐associated pulmonary fibrosis by activating TGF‐β1/IL‐11/MEK/ERK signaling, whether Sirt1 overexpression prevented TGF‐β1/IL‐11/MEK/ERK signaling‐mediated senescence‐associated pulmonary fibrosis in vitamin D‐deficient (Cyp27b1−/−)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 76 publications
2
22
0
Order By: Relevance
“…(34) Our recent study found that serum 1,25(OH) 2 D 3 levels decreased in physiologically aged mice compared with young mice, and VD deficiency induced senescence-associated pulmonary fibrosis. (33) Several lines of evidence suggest that 1,25(OH) 2 D 3 deficiency results in the development of age-related sarcopenia by inducing oxidative stress, muscle cell senescence, and SASP and by inhibiting skeletal muscle regeneration. (32,(35)(36)(37) Low 1,25(OH) 2 D 3 status is associated with decreased muscle strength and mass, which is improved by 1,25(OH) 2 D 3 supplementation, especially for an older population at high risk of sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…(34) Our recent study found that serum 1,25(OH) 2 D 3 levels decreased in physiologically aged mice compared with young mice, and VD deficiency induced senescence-associated pulmonary fibrosis. (33) Several lines of evidence suggest that 1,25(OH) 2 D 3 deficiency results in the development of age-related sarcopenia by inducing oxidative stress, muscle cell senescence, and SASP and by inhibiting skeletal muscle regeneration. (32,(35)(36)(37) Low 1,25(OH) 2 D 3 status is associated with decreased muscle strength and mass, which is improved by 1,25(OH) 2 D 3 supplementation, especially for an older population at high risk of sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Staining was performed as previously described. ( 4,33 ) Primary antibodies against NF‐κB‐p65 (No. 8242; Cell Signaling Technology, Beverly, MA, USA), IL‐1β (sc‐52012; Santa Cruz Biotechnology, Dallas, TX, USA), IL‐6 (sc‐1265; Santa Cruz Biotechnology Inc.), TNF‐α (sc‐52746; Santa Cruz Biotechnology), ATM (No.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, there is initial evidence that VitD contributes to the regulation of epigenetic mechanisms of aging and that VitD supplementation decelerates epigenetic aging in subjects with VDD [ 189 , 190 ]. Other mechanisms of aging that may be affected by VDD include sirtuin pathways [ 191 ] and cellular senescence [ 192 ]. There is also evidence supporting an association between VDD and frailty in aging [ 193 ].…”
Section: Vitamin D Deficiency Cerebrovascular Diseases Stroke and Vas...mentioning
confidence: 99%